Phase portrait analysis of super solitary waves and flat top solutions - Steffy, S.V.; Ghosh, S.S. (My University, 2018)
The phase portrait analysis of super solitary waves has revealed a new kind of intermediate solution which defines the boundary between the two types of super solitary waves, viz., Type I and Type II. A Type I super solitary wave is known to be associated with an intermediate double layer while a Type II solution has no such association. The intermediate solution at the boundary has a flat top structure and is called a flat top solitary wave. Its characteristics resemble an amalgamation of a solitary wave and a double layer. It was found that, mathematically, such kinds of structures may emerge due to the presence of an extra nonlinearity. Although they are relatively unfamiliar in the realm of plasma physics, they have much wider applications in other physical systems.
Keywords: Solitary waves; Super solitary waves; Sagdeev pseudopotential